Anomalous texture development induced by grain yielding anisotropy in Ni and Ni-Mo alloys. (November 2020) - Han, Lu; Jeurgens, Lars P.H.; Cancellieri, Claudia; Wang, Jing; Xu, Yifei; Huang, Yuan; Liu, Yongchang; Wang, Zumin
Abstract: During the annealing of Ni and Ni-Mo films, a 110 texture, usually considered to be both of high surface energy and high strain energy, was found to develop. Quantitative thermodynamic model calculations showed that the anomalous formation of this 110 texture originates fundamentally from the grain yielding anisotropy of Ni. Based on extensive grain yielding anisotropy model calculations, a "texture map" based on 111, 100, and 110 textures was constructed to predict the texture transition temperatures for different film thicknesses. A kinetic analysis of the texture evolution in the films is further presented, revealing that the texture evolution is controlled by the self-diffusion of atoms at grain boundaries. These findings pave the way for the achievement of unusual surface orientations through the quantitative texture design of thin films. Graphical abstract: Image, graphical abstract